Diversity Training: A Way to Increase Organizational Support for Sexual Minority Adolescents - Christine Regan; Mickie Swisher; Rosemary Barnett; Jane Luzar; Jeanna Mastrodicasa (EDIS, 2007)
FCS2268, a 3-page fact sheet by Christine Regan, Mickie Swisher, Rosemary Barnett, Jane Luzar, and Jeanna Mastrodicasa, is aimed at the staffs of organizations that serve youth. It discusses the importance of programs that are sensitive to the needs of sexual minority youth and gives a brief description of some possible diversity training exercises. Published by the UF Department of Family, Youth and Community Sciences, February 2007.